The Effectiveness of the Implementation of the Independent Learning Program-Independent Campus in Garut Regency - Ikeu Kania (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
Merdeka Learning-Independent Campus or known as MBKM, is the latest policy issued by the Ministry of Education and Culture to give birth to a superior generation. Campus Teaching is a form of student concern for the education of elementary school (SD) students both in rural and urban areas. This study aims to determine the effectiveness and constraints when implementing the Independent Learning Campus Teaching (MBKM) program in Garut Regency. The research method used is a qualitative research type. The results of research that have been carried out regarding the effectiveness of the implementation of the Independent Learning Campus Teaching (MBKM) program in Garut Regency in its implementation have not been effective enough. The lack of socialization and supervision indicates this during the implementation of the MBKM program.